The Effect of Ciprofloxacin Exposure on Ctx-M Gene Pattern of Escherichia Coli - Muhammad Amin1, Eddy Bagus Wasito1, Erwin Astha Triyono2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: An exposure of ciprofloxacin on Escherichia coli (E.coli) may cause cross-resistance to beta-lactam groups. The researchers obtained that ciprofloxacin, aminoglycoside, cotrimoxazole and second generation of cephalosporins were the risk factors for infection caused by Extended-Spectrum ?-Lactamases (ESBL)-producing bacteria. Exposure of ciprofloxacin to E.coli causes resistance of cefotaxime and produces ESBL which is genotypically evidenced by the presence of CTX-M.Objective: To know the effect of ciprofloxacin exposure on CTX-M gene pattern of E. coli.Method: A total of 30 E.coli isolates were exposed to ciprofloxacin for 14 days with the Kirby-Bauer antibiotic disc diffusion method. ESBL confirmatory test and Modified Double Disk Susceptibility Test (MDDST) method was used the antibiotic disc and continued electrophoresis using Polymerase Chain Reaction (PCR). The data analysis used the chi-square statistic test with ? = 0.05.Results: In the PCR examination, 10.00% of ESBL isolates were obtained to have CTX-M-15 gene, and 33.00% of non-ESBL E.coli isolates having CTX-M-15 gene. While 10.00% of E.coli ESBL isolates and 53.30% non-ESBL did not have CTX-M-15 genes. There was no significant difference between ciprofloxacin exposure and the presence of CTX-M-15 gene (p = 0.290).Conclusion: Most of the E.coli isolates had CTX-M-15 gene after the exposure. There was no difference in ciprofloxacin exposure to the presence of CTX-M-15 genes of E. coli.